A dynamic nanoconfinement strategy towards self-healing soft electronics with super stretchability, ultrahigh strength and reliably high conductivity. Issue 39 (21st September 2022) - Wang, Jun-Peng; Fu, Chuhan; Wu, Zehua; Lan, Hao; Cui, Siwen; Qi, Tao
Abstract : Herein, a nanoconfinement strategy is proposed to develop extremely deformable self-healing electrodes with ultrahigh strength and reliably high conductivity. Abstract : Functions of extreme stretchability, ultrahigh tensile strength, high-level conductivity and self-healing capacity endow polymer-based soft electronics with enhanced reliability and prolonged lifespan in deformable applications. However, it is still a huge challenge to achieve such a performance portfolio in individual electronic systems because ultrahigh strength is hardly compatible with self-healing ability in polymers. Herein, a hydrogen-bonded nanoconfinement strategy is proposed to synthesize supertough self-healing polyurethane (TSPU). The hierarchical hydrogen bonds, slight covalent crosslinking and rigid nanoconfinement phases result in self-healing polymers with super stretchability and ultrahigh strength. Self-healing soft electrodes were fabricated possessing the above functions simultaneously with the TSPU polymer as the supporting layer on which a eutectic gallium–indium (EGaIn) liquid metal is spread. By means of the dynamic nanoconfinement strategy, the soft electrodes showed a break elongation of ca. 2500% and a tensile strength of ca. 50 MPa, and 200 000 times its own weight could be lifted up. Remarkably, the resistance of the soft conductor only changed a little even at 2000% strain illustrating an outstanding conductive reliability. The ultrahigh strength, extreme ductility and high reliability bring self-healing electronics to a new high level. Such self-healing soft electronic devices could find promising potential in heavy-duty deformable electronic applications.